CDE Architecture Informed by Design Thinking for Rapid Design Change Propagation: A Socio-Technical Systems Approach to Cross-Border Construction - Vu, Ngoc Ha; Bui, Thi Kim Ngoc; Phuong, Kim Hoang Vuong; Ho, Truc Ngoc (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2026)
The Architecture, Engineering, and Construction (AEC) industry faces significant information latency in cross-border design change propagation, termed the "Latency Paradox". Employing Design Science Research (DSR) with a mixed-methods approach on a Vietnam-Australia project (X Group), this paper analyzes a critical 200mm reinforcement misalignment caused by reliance on asynchronous tools (email, PDF) and a prevalent "fear of error" culture. To address this, the study proposes a Common Data Environment (CDE) Reference Architecture integrating Design Thinking and Socio-Technical Systems theory. This architecture transforms the CDE into a "Living Model" with real-time Mobile-to-Model synchronization and a "blame-free" governance mechanism. Quantitative testing of 50 intervention events against a historical baseline, utilizing a novel T1-T4 scale, demonstrated significant improvements: Site-to-Design latency (T1 to T2: reporting receipt) reduced from a baseline median of 21.6 hours to 0.7 hours via mobile synchronization, while the resolution/instruction loop (T2-T3-T4: analysis and feedback) decreased from a baseline median of 44.2 hours to 5.5 hours, achieving a 98% propagation completion rate. The core contribution of this paper is providing a practical framework that effectively eliminates rework, while theoretically demonstrating the socio-technical operationalization of psychological safety within a digital environment to achieve cognitive alignment in global construction projects.